SWOT analysis and strategies to develop sustainable tourism in Bangladesh - Md. Sanaul Haque Mondal (UTMS Journal of Economics, 2017)
Bangladesh is a small country with enormous natural beauty and cultural attractions. These gorgeous natural and cultural traits make this country as one of the important tourist destinations in the world but, this potentiality has been overlooked. The tourism industry is facing several challenges, and development efforts of this industry are not sustainable. This paper maps out a way to sustainable growth of the tourism industry in Bangladesh using the SWOT (strengths, weaknesses, opportunities and threats) model and a derived matrix out of it. The data used for this study were derived from multiple sources, including literature review and interviews with professionals. To analyze strategic factors of the tourism industry in the country, internal strengths and weaknesses as well as external opportunities and threats were determined to be followed by development of strategic planning based on the SWOT matrix. Results showed that existing tourism activities in Bangladesh are unsustainable. To develop a sustainable tourism industry to attract tourists, this study suggests different WT (weaknesses- threats) strategies such as ensuring safety and security of tourists, effective planning for sustainable economic benefits, strict implementation of environmental regulations for ecological sustainability, alerting people about the importance of sustainable tourism development, and infrastructure development. Perhaps the findings of this study would be important in the effort to develop and promote a sustainable tourism industry in beautiful Bangladesh.
Keywords: L83; 330; weakness; threat; internal factor; external factor